Investigation of Thermal Comfort in Poultry Farm - Mohamed Lamine Bourabah; Said Menacer; Houssam Eddine Djani (University of Shahid Hama Lakhdar - El Oued, 2024)
Energy expenditure is the second highest expense for the poultry producers after the house mortgages, and is continuously on the rise. Energy related retrofits and renewable energy integration on a broiler farm can be very important to reduce the fossil energy use. The poultry growers need help in the on-farm energy use assessment and audit in order to optimize energy amount and cost. The main objective of this study is to confirm the applicability and the efficiency of geothermal heat exchangers coupling with the poultry house as function of time during the experiment on broiler farming. Farthermore, it can also allow to evaluate the level of the thermal comfort conducted by the geothermal heat exchangers throught several parametres such as humidity, internal temperature, CO2 and CO emission. The obtained results shouw that the proposed geothermal system effects on all these parametres.
Mémoire de Master spécialisé en énergie
Keywords: Poultry House; Thermal Comfort; humidity; internal temperature; CO2 emission.; بيت الدواجن، الراحة الحرارية، الرطوبة، درجة الحرارة الداخلية، انبعاث ثاني أكسيد الكربون.